The Total Antioxidant Capacity and its Relationship with Atherosclerosis Risk Factors in a Sample of Iraqi Individuals with Type 2 Diabetes Mellitus - Idan, Hasan H.; Mohamoud, Halla G. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Diabetes mellitus is significantly related to cardiovascular disease, such as atherosclerosis. Antioxidants are essential in the prevention of atherosclerosis by a variety of mechanisms, which encompass the suppression of free radical production, inhibition of low-density lipoprotein oxidation, and prevention of atherosclerotic plaque formation.Objectives: This study aims to evaluate the levels of total antioxidant capacity and malondialdehyde as oxidative stress indicators in Iraqi type 2 diabetes mellitus (T2DM) patients and investigate their relationship with atherosclerotic risk factors.Methods: This case-control study took place between October 2023 to January 2024 at Al-Karkh General Hospital in Baghdad. The study included a total of 130 participants: 70 individuals diagnosed with T2DM and 60 healthy controls were recruited from relatives of patients attending the hospital and hospital employees who did not have T2DM. The two study groups were age-matched. Blood samples from both groups were analyzed to determine the following parameters: Lipid profile, total antioxidant capacity (TAC), Malondialdehyde (MDA) as an oxidative stress marker, glycated hemoglobin (HbA1c), and atherogenic indices (e.g. atherogenic index of plasma).Results: The mean serum total antioxidant capacity (TAC) in the T2DM group was significantly lower than the control group (46.9 ± 5.05 U/mL vs. 70.8 ± 4.71 U/mL). This indicates a highly significant difference between the groups. Additionally, in the T2DM group, statistically significant inverse correlations were observed between TAC and most of the measured lipid profile parameters, HbA1c, and atherogenic indices.Conclusions: Low TAC may be a potential predictor of atherosclerosis in Τ2DM patients and highlight the relationship between oxidative stress, lipid metabolism, and thermogenesis.